LA GESTION DE L’ENVIRONNEMENT URBAIN A BRAZZAVILLE: PROBLEMES ET PERSPECTIVES - Kevin, Nzoussi Hilaire; Feng, Li Jiang (European Scientific Journal, ESJ, 2014)
With growth of over 4% per year, African city in general and in particular Congolese (Brazzaville) face the rural exodus which becomes an inevitable phenomenon nowadays. The increase of the population of Brazzaville foreshadows an increase in demand for services and goods at all levels including environmental pressures resulting from human activities and degradation of the urban environment. Brazzaville is the corollary of several factors that require adequate resources to cope; this implies the establishment of a necessary environmental policy in order to save the people from environmental dangers.